Performance of Textured Metallized Teflon Coverings with High Diffuse Reflectance Coefficient in Low Earth Orbit on ISS - Jacob Kleiman (Mechanics and Advanced Technologies, 2019)
Abstract. The data of mathematical modeling of the thermal state of a cutting tool under conditions of laser hardening are presented. The features of the implementation of the method of polyargument systems for solving the three-dimensional heat transfer problem with a localized movable laser heating source are considered. The data of numerical studies to establish patterns of the influence of the radius of the heating spot on the temperature regime of the hardened tool are presented. It is shown that varying this parameter can be used as an effective way of influencing the thermal state of a cutting tool during its hardening by a laser beam. The results of modeling the temperature conditions of the tool in a wide practically important range of changes in its sharpening angle are presented.